El efecto de la temperatura en la determinación sexual del pez blanco de Pátzcuaro Chirostoma estor (Jordan, 1880) - Corona Herrera, Guillermo Armando (Universidad Michoacana de San Nicolás de Hidalgo, 2013)
Chirostoma estor is an endangered freshwater atherinopsid endemic to central Mexico. In this work we investigated the prescence of temperature-dependent sex determination (TSD) mechanisms that could be applied as a biotechnological tool for sex control in the culture of this species. This information could be useful also as a bioindicator of anthropogenic or climate change effects on its reproduction. For this work gametes from three single pair broods were manually fertilized, immediately divided in three groups, and incubated at 14, 21, and 29ºC. These thermal treatments were continued through hatching until 30 days after hatching (dah). All groups were then transferred to 21ºC. About 40-60 fish per treatment were sampled at 90 dah and processed histologically to determine phenotypic sex ratios. Also to determine the onset of sexual histological differentiation at 21ºC we sampled 20 larvae each week from hatching to 30 dah. The proportions of males for the first brood were 67, 65 and 90% (p≤0.01), to second brood, 57, 55 and 64 % (p≥0.05), and to the third brood 48, 75 and 92%(p≤0.01); at 14, 21, and 29oC respectively. Thermal treatments applied from fertilization show a clear effect in biased phenotypic sex ratios in brood 1 and 3, wich translates to substantial differences in the response of each brood to temperature. The histological differentiation onset was determined at 30 dah showing presumptive testis and ovaries with presence of somatic and primordial germ cells and the opening of the primordial ovarian cavity. These results suggest that incubation at high temperatures during embryonic development can lead to male-biased sex ratios in this species. The effects of lower and medium temperatures were not so clear, suggesting a mixture of genotypic and TSD mechanisms in C. estor as in other atherinopsids. Moreover, the histological differentiation onset was observed around 30 dah and suggests that molecular differentiation occurs early in the first larvae stages, however more studies are required to clarify the gonadal development in this important species.

El pez blanco de Pátzcuaro Chirostoma estor es una especie endémica en peligro de extinción con un alto valor social, económico, ambiental y cultural del altiplano Mexicano. El presente trabajo fue realizado con el fin de obtener información científica sobre la determinación sexual por temperatura (DST) en esta especie, este conocimiento puede aplicarse como una herramienta biotecnológica para el control de la proporción sexual fenotípica en un cultivo comercial, así como para evaluar los efectos del cambio climático y la influencia antropogénica sobre la reproducción del pez blanco en el medio natural. A partir de 3 parejas de reproductores se obtuvieron gametos sexuales que fueron manualmente fecundados, inmediatamente después se dividieron en tres grupos y se incubaron a 14, 21 y 29ºC. Estos tratamientos térmicos se continuaron hasta 30 días post eclosión (dpe), posteriormente todos los grupos fueron trasladados a 21ºC hasta los 90 dpe. Al finalizar el experimento 40-60 peces por tratamiento fueron muestreados y procesados histológicamente para evaluar la proporción sexual fenotípica. Para determinar el inicio de la diferenciación sexual histológica a los 21ºC se muestrearon semanalmente 20 larvas desde la eclosión hasta 30 dpe. La proporción de machos para la primera progenie fueron 67, 65 y 90%(p≤0.01) para la segunda progenie, 57, 55 y 64% (p≥0.05) y la tercera progenie 48, 75 y 92%(p≤0.01) en 14, 21 y 29oC respectivamente. Los tratamientos térmicos aplicados desde la fertilización demuestran una influencia clara sobre la proporción sexual fenotípica para las parejas 1 y 3, por lo que la respuesta de cada progenie a la temperatura es significativamente diferente. El inicio de la diferenciación histológica fue determinado en el día 30 post eclosión con la presencia de testículos y ovarios en fase inicial de desarrollo, con la presencia de células germinales primordiales, somáticas y la apertura de la cavidad ovárica primordial.
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; IIAF-M-2013-0483; Temperatura; Determinación sexual; Pez blanco; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1872